2007
DOI: 10.1093/jat/31.9.588
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Methylphenidate in the Hair of Children Treated with Ritalin*

Abstract: Hair samples were collected from 17 children (7-16 years of age) who had received methylphenidate therapy on a long-term basis. The dose was 10-60 mg per day. To 20 mg of pulverized hair, phosphate buffer and internal standard (norpethidine) were added. Extraction was performed by ultrasonic treatment, followed by isolation by alkaline extraction with isohexane. Derivatization with N-Methyl-bisheptafluorobutyric amide enabled gas chromatography-mass spectrometry analysis of the perfluorobutyryl derivatives in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…In accordance with the fact that acidic substances are incorporated to a much lesser extent than basic compounds in the hair matrix, preliminary observations [2,4] showed that ritalinic acid is absent in hair from treated subjects.…”
Section: Detection In Hairmentioning
confidence: 63%
See 2 more Smart Citations
“…In accordance with the fact that acidic substances are incorporated to a much lesser extent than basic compounds in the hair matrix, preliminary observations [2,4] showed that ritalinic acid is absent in hair from treated subjects.…”
Section: Detection In Hairmentioning
confidence: 63%
“…Parent from chronic exposed children [2,4], the measured concentration can be considered as very low. Segmental analyses demonstrated that only the proximal segment tested positive for MPH.…”
Section: Compoundmentioning
confidence: 99%
See 1 more Smart Citation
“…Gas chromatography-mass spectrometry [10,11], HPLC-UV [12][13][14], -fluorescence (-FL) detections [15], liquid chromatography (LC-MS) [5,[7][8][9]16,17] and LC-tandem mass spectrometry (LC-MS/MS) [2,18,19] methods were widely used. Quite recently, MS detection for very low-level quantification of MPH in biological samples has been frequently used.…”
Section: Introductionmentioning
confidence: 99%
“…Marchei et al [9] published a procedure using liquid chromatography (LC) coupled to mass spectrometry (MS), which had a limit of detection of 50 pg/ mg. Sticht et al [10] used gas chromatography coupled to MS, including a derivatization step, with a limit of detection of 20 pg/mg. Because the measured concentrations in hair are as low as less than 1 ng/mg, even after chronic daily exposure [10], any method devoted to testing for MPH in hair after a single ingestion should be highly sensitive. We present here an assault case, in which the claim of a single use of MPH was supported after analysis of hair segments by ultrasensitive LC-MS-MS.…”
Section: Introductionmentioning
confidence: 99%